Explanation:
I'm going to give you the explanation first.
Let's start by making the equations more manageable.
![y=(x)/(2) \\2y=x\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/wnlfxs4s78bmynq1ac51hs3n9i8fugag4m.png)
There you are for the first.
Now insert that value into the second:
![2x^(2) -y^2=7\\2(2y)^2-y^2=7\\4y^2-y^2=7\\3y^2=7\\y^2=(7)/(3) \\y=+or-\sqrt{(7)/(3) }](https://img.qammunity.org/2021/formulas/mathematics/high-school/4s1a9tz9w9p8jkkztv8m69qu56uj4wno9p.png)
We now have the value for y, and can solve for x.
Can you solve for x on your own?
Feel free to comment with questions. Have a great day!